2012
DOI: 10.1371/journal.pone.0031890
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Proliferation and Antigen Presentation Activity following Internalization of Polydispersed Carbon Nanotubes by Primary Lung Epithelial Cells

Abstract: Interactions between poly-dispersed acid functionalized single walled carbon nanotubes (AF-SWCNTs) and primary lung epithelial (PLE) cells were studied. Peritoneal macrophages (PMs, known phagocytic cells) were used as positive controls in this study. Recovery of live cells from cultures of PLE cells and PMs was significantly reduced in the presence of AF-SWCNTs, in a time and dose dependent manner. Both PLE cells as well as PMs could take up fluorescence tagged AF-SWCNTs in a time dependent manner and this up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In a recent study, we have demonstrated that mouse lung epithelial cells may present mycobacterial antigens to sensitized T helper cells through Class II MHC presentation pathway and this presentation is significantly suppressed by AF-SWCNTs (Kumari and Saxena, 2011;Kumari et al, 2012). In the present study, we have extended the research to examine if CD1d lipid presentation takes place in LA-4 lung epithelial cells and to assess the effect if any, of AF-SWCNTs on this process.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 77%
“…In a recent study, we have demonstrated that mouse lung epithelial cells may present mycobacterial antigens to sensitized T helper cells through Class II MHC presentation pathway and this presentation is significantly suppressed by AF-SWCNTs (Kumari and Saxena, 2011;Kumari et al, 2012). In the present study, we have extended the research to examine if CD1d lipid presentation takes place in LA-4 lung epithelial cells and to assess the effect if any, of AF-SWCNTs on this process.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 77%
“…5a and 5b demonstrate a substantial increase in activity of COX-2 on treatment with autoclaved BCG, which was significantly abrogated on treatment with AF-SWCNTs; the decline being 21% (p<0.05) and 85% (p<0.05) in RAW 264.7 and MH-S cells respectively. Our previous work on AF-SWCNTs has shown that it suppresses B, T and NK cell function and processing and presentation of antigens by macrophages as well as lung epithelial cells [14,12,13,16,15,10]. These studies therefore may suggest that AF-SWCNTs may be a good candidate as a general immunosuppressive agents and perhaps as anti-inflammatory agents.…”
Section: Modulation Of Expression Of Bcg Induced Cox-2 By Af-swcnts Umentioning
confidence: 89%
“…Our group has been studying the interactions of AF-SWCNTs with several biological systems, and have demonstrated modulatory effects of AF-SWCNTs on activation and functioning of T cells [12,13], B cells [13,14], antigen presenting cells [15,16], hematopoietic activity in bone marrow [7, 17] and lung epithelial cells [18,15,16]. Since AF-SWCNTs have suppressive effect on many components of the immune system, we hypothesized that AF-SWCNTs may also have a generalized anti-inflammatory effect.…”
Section: Af-swcnts Unlike Swcnts Interact Efficiently With the Cellsmentioning
confidence: 99%
“…Acid functionalization of single-walled CNTs significantly reduces their in vivo toxicity (Schipper et al, 2008) and enhances their interaction with immune cells , Gazia and El-Magd, 2019. Previous studies have shown that the acid functionalized SWCNTs (AF-4 SWCNTs) modulate erythropoiesis (Bhardwaj and Saxena, 2015, Md and Saxena, 2018, Sachar and Saxena, 2011, downregulate protein and lipid antigen presentation (Rizvi et al, 2015, Kumari et al, 2012, alters epithelial tight junctions (Singh et al, 2020), reduce dendritic cells polarization capacity (Aldinucci et al, 2013), suppress activation of NK cells (Alam et al, 2016) and generation of alloimmune cytotoxic T cells (Alam et al, 2013, Dutt and.…”
Section: Introductionmentioning
confidence: 99%